2018
DOI: 10.3389/fimmu.2018.02310
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Complement System Transcripts in Chronic Antibody-Mediated Rejection and Recurrent IgA Nephropathy in Kidney Transplantation

Abstract: Background: The complement system activation and regulation have been linked to post-transplant pathologies including chronic antibody mediated rejection (cAMR) and the recurrence of IgA nephropathy (ReIgAN) but distinct mechanisms remain to be elucidated.Methods: In this retrospective single center study, the outcome of kidney transplantation was studied in 150 patients with late histological diagnosis to be either cAMR or ReIgAN, 14 stable kidney grafts at 3 months and finally 11 patients with native kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The expressions of the SH2D1B, CX3CR1, IGHG1, IRF4, MS4A1, C5, CD46, and TGFB1 transcripts were higher in the TI of patients with chronic active ABMR; only the expression of the CD14 gene predominated in the glomeruli. The upregulation of complement-associated gene transcripts in chronic ABMR was just recently reported (35). In our study, we showed the TI as a source of upregulated transcripts, including complement ones, in chronic active ABMR.…”
Section: Discussionsupporting
confidence: 82%
“…The expressions of the SH2D1B, CX3CR1, IGHG1, IRF4, MS4A1, C5, CD46, and TGFB1 transcripts were higher in the TI of patients with chronic active ABMR; only the expression of the CD14 gene predominated in the glomeruli. The upregulation of complement-associated gene transcripts in chronic ABMR was just recently reported (35). In our study, we showed the TI as a source of upregulated transcripts, including complement ones, in chronic active ABMR.…”
Section: Discussionsupporting
confidence: 82%
“…The study showed that defective peripheral CD46 gene expression did not correlate with eGFR at sampling, but with a faster annual loss of GFR [ 65 ]. Similarly, Cernoch et al [ 66 ], in a retrospective study of kidney-transplanted patients with IgAN recurrence, showed that there were no associations of eGFR with intrarenal CD46 complement transcripts, however they did describe the association of several intrarenal gene transcripts, including CD55, with CKD stage. In addition, new data coming from genetic and clinical studies are demonstrating a pivotal role of factor H and complement factor H–related proteins (CFHR) in IgAN development and progression [ 67 , 68 ] Deletion of CFHR1–3 was demonstrated to be protective in IgAN and these molecules are competitors of factor H and can efficiently lead to uncontrolled complement activation [ 56 , 69 ].…”
Section: Mechanism Of Diseasementioning
confidence: 99%
“…The first in vivo studies showed that overexpression of human CD55 and CD59 (hCD55, hCD59) protects mice from impaired kidney function in an experimental renal I/R injury model (Bongoni et al, 2017). A recent retrospective study of 150 patients after kidney transplantation, confirmed that lower intragraft expression of CD55 is a risk factor for rapid progression of chronic renal rejection (Cernoch et al, 2018). A more detailed study of kidney transplantations demonstrated a correlation between promotor polymorphisms in complement-regulatory proteins and graft survival (Michielsen et al, 2018).…”
Section: Accommodation: the Role Of Protective Gene Expression In Ecsmentioning
confidence: 99%